2021
DOI: 10.1016/j.apcata.2020.117906
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt catalysts on carbon-based materials for Fischer-Tropsch synthesis: a review

Abstract: Highlights Challenges and opportunities in Co/C catalyzed Fischer-Tropsch synthesis  Guidelines for the design of Co/C catalysts for Fischer-Tropsch synthesis  The choice of carbon materials as Fischer-Tropsch synthesis support is rationalized  The evolution of TOF and SC5+ with Co particle size is relatively complex  Effect of confinement and spillover on catalyst performances are discussed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 298 publications
(574 reference statements)
1
29
0
Order By: Relevance
“…Oxide supports such as SiO 2 , Al 2 O 3 or TiO 2 are generally employed to stabilize cobalt particles, but they present the drawback of undesirable strong cobalt-support interactions that lead to the formation of non-reducible and inactive mixed metal oxides [4]. Such detrimental interactions can be circumvented by using carbon materials as support modifier [6,7] or directly as support [8], since their interaction with cobalt is weaker, which facilitates metal reduction. Additionally, the good thermal conductivity of some sp 2 carbon materials, such as carbon nanotubes (CNT) enables to limit methane formation and catalyst deactivation, by avoiding the formation of hot spots resulting from the high exothermicity of the FT reaction.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Oxide supports such as SiO 2 , Al 2 O 3 or TiO 2 are generally employed to stabilize cobalt particles, but they present the drawback of undesirable strong cobalt-support interactions that lead to the formation of non-reducible and inactive mixed metal oxides [4]. Such detrimental interactions can be circumvented by using carbon materials as support modifier [6,7] or directly as support [8], since their interaction with cobalt is weaker, which facilitates metal reduction. Additionally, the good thermal conductivity of some sp 2 carbon materials, such as carbon nanotubes (CNT) enables to limit methane formation and catalyst deactivation, by avoiding the formation of hot spots resulting from the high exothermicity of the FT reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The principal identified Co/C catalyst features influencing the catalyst performances are: i) the Co particle size; ii) the Co reducibility; iii) the cobalt phase (fcc or hcp); and iv) the confinement of cobalt particles (particularly in CNT) [8]. Recently, we also reported that hydrogen spillover from the cobalt particles to the carbon support can also contribute to the enhancement of Co/C catalytic activity [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations